Evaluasi Fungsi Pedestrian di Kesawan dalam Mendukung Kawasan Heritage Kota Medan - Ardhanajaya, Henrico Paul; Rambe, Yunita Syafitri (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Historic areas play an important role in the cultural and architectural identity of a region. In a historic area, the local government, in this case BPK2LK, conserves historical relics not only in the old building rows, but also in the surrounding area. This aims to provide an area identity to revive and improve the area's economy. In the Kesawan area which is one of the historical areas, the implementation of revitalization of the area by widening the pedestrian area. This is to provide comfort and activate the pedestrian function as a support for the historic tourism area in Kesawan. But an evaluation study is needed on the effectiveness of the function of the pedestrian path, on the basis of observations there are several congestion problems due to smaller vehicle lanes and the quantity of vehicles that increase every day. Another problem is that there is no bus stop, so public transportation uses the road to lower and raise passengers. Pedestrians who are already larger and more comfortable, have not increased the quantity of pedestrians. The purpose of this study was to assess the effectiveness of the success of the pedestrian function in the Kesawan area after the pedestrian area underwent reconstruction. Research methods carried out with qualitative and quantitative approaches through field surveys, interviews, questionnaires, statistical data processing. The analysis was carried out using SWOT analysis to get a comprehensive picture of the strengths, weaknesses, opportunities, and threats in the function of pedestrian paths in historic areas. The research output shows the success of changes to road widening in the pedestrian area in Kesawan which shows 85% stated that pedestrians in the area feel comfortable with the presence of street furniture. This facility allows pedestrian users to enjoy the historic area in the area. However, there are still some shortcomings such as poor facilities such as the lack of trash bins that make this area less clean. Nevertheless, this widening area can be recommended to the community to maximize the use of pedestrians.